Evaluating self-defence claims in the United Nations collective security system: between esotericism and exploitability - Roele, Isobel (2009)
This thesis is about identifying valid self-defence claims in the UN collective security system. The thesis suggests a fresh theoretical approach to balancing the imperative for adaptation of the right of self-defence with the danger that too broad a right could be exploited by states wishing to justify national policy. The starting point for the thesis is the twin realist criticisms that the right of self- defence is either too narrowly drawn and therefore not fit for the purpose of protecting states‘ interests, or too broadly drawn and therefore hostage to the subjective interpretation of states using force. These problems were intensified during the Administration of former President G.W. Bush in the USA. In this work, these two criticisms are dubbed 'esotericism' and 'exploitation' respectively.